New synonym of Nephus (Nephus) voeltzkowi Weise (Coleoptera: Coccinellidae), with comments on the origin of a Neartic population and its possible asexual status - Magro, Alexandra; Almeida, Lúcia M.; Churata-Salcedo, Julissa; Hemptinne, Jean-Louis (Zootaxa, 2021)
Coccinellidae (Coleoptera), commonly known as ladybirds or ladybugs, are a highly diversified family comprising nearly 6000 described species (Vandenberg 2002) distributed in 2 subfamilies and 24 tribes (Seago et al. 2011). The genus Nephus Mulsant, 1846, present worldwide, is currently placed in the vast Coccidulini tribe (Seago et al. 2011). There are different classifications for Nephus: Gordon (1976, 1985) considered five Nephus subgenera (Depressoscymnus Gordon, Nephus Mulsant, Scymnobius Casey, Sidis Mulsant, and Turboscymnus Gordon), while Fürsch (1987) considered nine Nephus subgenera, and later (Fürsch 1996) excluded Diomus Mulsant, 1850 as subgenus, leaving Bipunctatus Fürsch, 1987, Depressoscymnus Gordon, 1976, Geminosipho Fürsch, 1987, Nephus Mulsant, 1846, Parascymnus Chapin, 1965, Scymnobius Casey, 1899, Sidis Mulsant, 1850 and Turboscymnus Gordon, 1976. Gordon and González (2002) elevated Scymnobius to genus.